Microbial quality of hilsa shad (Tenualosa ilisha) at different stages of processing (Journal of the Bangladesh Agricultural University, 2012)
An attempt was made from October 2008 to March 2009 in a fish processing industry of Bangladesh (the Sea    Resource Limited, Sadarghat, Chittagong) to determine microbial quality of Tenualosa ilisha at different stages of    processing. During this investigation Escherichia coli, fecal coliform, vibrio cholerae, Salmonella and total load of    bacteria were identified from 5 stages of processing. Those stages were receiving, primary washing stage with 5PPM  chlorine water, final washing stage with 10 PPM chlorine water, after blast freezing at -40 ± 20C and finally after one    month storage at -18 ± 20,/sup>C. It was observed that 80.69 % of total bacterial load, 77.29% of total coliform and 58.33 %    of fecal coliform were destroyed during different processing stages. There was no evidence of presence of    Salmonella and Vibrio cholera at any stages of processing. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11049 J. Bangladesh Agril. Univ. 9(2): 339344, 2011